Raising Children to Work Hard: Altruism, Work Norms, and Social Insurance - Lindbeck, A.; Nyberg, S. (Quarterly Journal of Economics, 2006)
Empirically, disincentive effects on work of generous welfare state arrangements tend to appear with a substantial time lag. One explanation is that norms concerning work and benefit dependency delay such effects. We model altruistic parents' economic incentives for instilling such work norms in their children. Anticipated economic support from parents may reduce work effort, and parental altruism makes threats to withdraw such support noncredible. Instilling norms mitigates this problem. However, generous social insurance arrangements tend to weaken parents' incentives to instill such norms in their children. We find empirical support for this prediction.